Hubungan Perilaku Pengobatan Dan Aktivitas Fisik Dalam Brief Counseling Farmasis Pada Pasien Hipertensi Di RSUD Ulin Banjarmasin - Saftia Aryzki; Noverda Ayuchecaria (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background : Hypertension is a non-communicable disease. As many as 1 billion people in the world or 1 in 4 adults suffer from this disease. In fact, it is estimated that the number of people with hypertension will increase to 1.6 billion by 2025. Patient behavior by implementing controlled patient blood pressure will help achieve the success of patient therapy. Research Purposes: The purpose of the study was to determine the relationship between the level of treatment behavior with physical activity in hypertensive patients at Ulin Hospital Banjarmasin. Methods: This research is a quasi-experimental study using two groups with the method of taking the sample by using a simple random sampling method that meets the inclusion and exclusion criteria. The sample in this study was 60 samples with 30 samples in the control group and 30 samples in the intervention group. This research was conducted at the Internal Medicine Polyclinic of Ulin Hospital from March-June 2020. The data collection technique used in this study was a behavioral level questionnaire, the International Physical Activity Questionnaire (IPAQ) and blood pressure questionnaires taken from medical records. Results: The results of the normality test indicate that the data is not normally distributed, so a non-parametric test will be carried out, namely the Spearman Correlation test. The results of the Spearman Correlation test between treatment behavior and physical activity after giving treatment had a correlation relationship with the category quite strong and the significance result was 0.006 (p <0.05). This means that there is a strong relationship between treatment behavior and physical activity for hypertensive patients. Conclusion: treatment behavior with physical activity after treatment has a correlation with the category is quite strong and the result is a significance of 0.006 (p <0.05).Keywords : Medication Behavior, Patient Activity, Hypertension, Relationship